2009
DOI: 10.1103/physrevlett.102.052301
|View full text |Cite
|
Sign up to set email alerts
|

Double-Pionic Fusion of Nuclear Systems and the “ABC” Effect: Approaching a Puzzle by Exclusive and Kinematically Complete Measurements

Abstract: The ABC effect-a puzzling low-mass enhancement in the pipi invariant mass spectrum, first observed by Abashian, Booth, and Crowe-is well known from inclusive measurements of two-pion production in nuclear fusion reactions. Here we report on the first exclusive and kinematically complete measurements of the most basic double-pionic fusion reaction pn-->dpi;{0}pi;{0} at beam energies of 1.03 and 1.35 GeV. The measurements, which have been carried out at CELSIUS-WASA, reveal the ABC effect to be a (pipi)_{I=L=0} … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
123
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(133 citation statements)
references
References 34 publications
9
123
1
Order By: Relevance
“…Recently, the WASA detector at COSY confirmed their early observations of the d * (2380) [1][2][3][4]6]: to explore the nature of the ABC effect [7], they measured the polarized np scattering, and their partial-wave analysis exhibited a resonance pole at (2380 ± 10 − i40 ± 5) MeV with quantum numbers I(J P ) = 0(3 + ) [5]. The d * (2380) may be a ∆∆ dibaryon or a six-quark state, first predicted on the basis of SU (6) symmetry by Dyson and Xuang in 1964 [8].…”
Section: Introductionmentioning
confidence: 83%
“…Recently, the WASA detector at COSY confirmed their early observations of the d * (2380) [1][2][3][4]6]: to explore the nature of the ABC effect [7], they measured the polarized np scattering, and their partial-wave analysis exhibited a resonance pole at (2380 ± 10 − i40 ± 5) MeV with quantum numbers I(J P ) = 0(3 + ) [5]. The d * (2380) may be a ∆∆ dibaryon or a six-quark state, first predicted on the basis of SU (6) symmetry by Dyson and Xuang in 1964 [8].…”
Section: Introductionmentioning
confidence: 83%
“…The systematic studies of the π 0 π 0 production [5] by the WASA collaboration indeed revealed a resonance-like feature in the total cross section in n-p reactions at energies below the ∆∆ excitation associated with an unexpected enhancement at low ππ invariant mass, this is called the ABC effect. The effect appears in the di-pion isospin 0 channel and cannot be described by channels like ∆∆ or N*(1440).…”
Section: Pn → Dπ + π − Exclusive Analysismentioning
confidence: 99%
“…The effect appears in the di-pion isospin 0 channel and cannot be described by channels like ∆∆ or N*(1440). To explain the experimental results, a di-baryon resonance (d*) has been proposed with the width of 70 MeV and a pole mass of 2380 MeV [5]. The excitation of such a six-quark object should also be visible in the reaction pn → dπ + π − , which is an admixture of isospin 0 and 1 states.…”
Section: Pn → Dπ + π − Exclusive Analysismentioning
confidence: 99%
See 2 more Smart Citations